Effect of magnesium niobate precursors on phase formation, microstructure and dielectric properties of perovskite lead magnesium niobate ceramics - R. Wongmaneerung (2018)
Lead magnesium niobate, Pb(Mg1/3Nb2/3)O3 or PMN, ceramics were fabricated by using B-site precursor method where both MgNb2O6 and Mg4Nb2O9 were employed as magnesium niobate precursors. It has been found that under suitable sintering condition highly dense and pure Pb(Mg1/3Nb2/3)O3 ceramics can be successfully achieved in both processing routes. In addition, pure perovskite Pb(Mg1/3Nb2/3)O3 ceramic with slightly higher dielectric constant can be produced at lower sintering temperature by using a corundum-route. © 2008 Elsevier B.V. All rights reserved.